1997
DOI: 10.3126/jngs.v15i0.32121
|View full text |Cite
|
Sign up to set email alerts
|

Sediment - ostracode relationship in the gulf of Mannar, off Toticorin, east coast of India

Abstract: An attempt has been made to establish the sediment-ostracode relationship, in the gulf of Mannar, off Tuticorin, south east coast of India. 48 sediment samples were collected from 12 sampling stations. Twelve bottom sediment samples were collected once in three months, for a period of one year, so as to represent the four seasons (winter, summer, southwest Monsoon and northeast Monsoon). Calcium carbonate and organic matter content of each sample were correlated against the ostracode population recovered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The association of CaCO3 with sand fractions is indicating its association with sand fraction. Similarly, Hussain et al (1997) also observed a relationship between CaCO3 and sand fractions in the Gulf of Mannar sediments, off Tuticorin. The calcium carbonate percentage in the sediment cores ranges from 0.5 to 5.5 % (Table 1), which is higher particularly in the top portion of the core between 0 and 25 cm.…”
Section: Sediment Characteristics Calcium Carbonate (Caco3)mentioning
confidence: 60%
“…The association of CaCO3 with sand fractions is indicating its association with sand fraction. Similarly, Hussain et al (1997) also observed a relationship between CaCO3 and sand fractions in the Gulf of Mannar sediments, off Tuticorin. The calcium carbonate percentage in the sediment cores ranges from 0.5 to 5.5 % (Table 1), which is higher particularly in the top portion of the core between 0 and 25 cm.…”
Section: Sediment Characteristics Calcium Carbonate (Caco3)mentioning
confidence: 60%
“…The observations acquired from the surface ornamentation of ostracod carapaces can directly be related to their substrate type. The majority of the specimens from the current study have ornate, often heavily calcified carapaces, which suggests that they are typically found in sandy substrates and high-energy shallow water environments (Hussain et al, 1997).…”
Section: Resultsmentioning
confidence: 91%
“…Instead of rock weathering, the primary source of carbonate may be the precipitation of CaCO 3 by marine organisms. Hussain et al (1997) observed a relative decrease in the organic matter along with an increase in the CaCO 3 content of the sediments patronising a maximum population of Ostracoda in the Gulf of Mannar, off Tuticorin. However, there is no proper correlation between sediment parameters and total population in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations